Platelet Protease Activated Receptor 1 Is Involved in the Hemostatic Effect of 20(S)-Protopanaxadiol by Regulating Calcium Signaling - Zhang, He; Pan, Daian; Wu, Xingquan; Su, Wenjie; Tang, Xiaolei; Zhao, Daqing; Sun, Liwei; Song, Bailin; Bai, Xueyuan; Li, Xiangyan (Frontiers in Pharmacology, 2020)
Panax notoginseng (Burk.) F.H. Chen has long been used to stop bleeding for hundreds of years in China. At present, only dencichine and notoginsenoside Ft1 showed hemostatic effect. Other ingredients from Panax notoginseng need to be further investigated. The study aims to evaluate the hemostatic effect of 20(S)-protopanaxadiol (PPD) and reveal its mechanism. The bleeding time was measured in mouse tail amputation and liver scratch models. The routine blood and plasma coagulation parameters were measured using blood analyzer. Platelet aggregation rate and ATP release were analyzed by platelet aggregometer. Subsequently, degranulation marker CD62p and PAC-1, and the concentrations of cytosolic Ca2+ ([Ca2+]i), cAMP and cGMP concentrations were also assessed. We found that PPD shorted bleeding time on the mouse tail amputation and liver scratch models and mainly increased blood platelet count in the rats after subcutaneous injection of 4 h. Meanwhile, PPD decreased APTT, increased FIB content and directly induced platelet aggregation. In the absence of Ca2+, PPD induced the increase of [Ca2+]i and slightly increased the levels of CD62P and PAC-1. After the addition of Ca2+, PPD treatment markedly promoted platelet activation by promoting ATP level, releasing CD62P and increasing PAC-1 binding in washed platelets. Excitingly, PPD-induced changes including platelet aggregation, decreased cAMP content, and the increases of CD62P and PAC-1 were significantly reversed by protease-activated receptor 1 (PAR-1) antagonist, vorapaxar, which showed similar function as thrombin. PPD is an essential hemostatic ingredient in Panax notoginseng for promoting hematopoiesis and thrombopoiesis. PAR-1 is involved in PPD-induced platelet aggregation by regulating calcium signaling, which could contribute to the new insight for the treatment of hemorrhagic disease.